2011
DOI: 10.1063/1.3641861
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid functional study of Si and O donors in wurtzite AlN

Abstract: The properties of Si and O donors in wurtzite AlN have been studied by means of hybrid functional calculations, finding that both impurities form DX centres. In the case of Si, the stable DX centre is close in energy to the substitutional donor state and to a second metastable DX centre, thus explaining both the persistent effects and the broad range of activation energies observed experimentally. Ionisation energies have been computed for both Si and O donor states.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
40
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 26 publications
(29 reference statements)
3
40
0
Order By: Relevance
“…25 More recent hybrid functional calculations suggest that both Si and O are DX centers in AlN. 26 In this letter, we report EPR study of Al x Ga 1Àx N:Si with x $ 0.77. By monitoring the change of the concentration of the neutral state d 0 with temperature in darkness, we show that Si already becomes a DX center as previously suggested by Bayerl and co-workers 21 but behaves as a shallow donor due to a small separation of only $3 meV between the DX À and d 0 states, and its shallow states follow the effective mass theory (EMT).…”
Section: 10mentioning
confidence: 80%
“…25 More recent hybrid functional calculations suggest that both Si and O are DX centers in AlN. 26 In this letter, we report EPR study of Al x Ga 1Àx N:Si with x $ 0.77. By monitoring the change of the concentration of the neutral state d 0 with temperature in darkness, we show that Si already becomes a DX center as previously suggested by Bayerl and co-workers 21 but behaves as a shallow donor due to a small separation of only $3 meV between the DX À and d 0 states, and its shallow states follow the effective mass theory (EMT).…”
Section: 10mentioning
confidence: 80%
“…In the neutral charge state d 0 , a Si donor prefers to capture another electron and undergoes a large lattice relaxation, relaxing to its lower-lying negatively charged state DX À according to the process: 10,11 have found two configurations of Si DX donors: a stable DX 1 center with the broken Si-N bond along the c axis and a metastable DX 2 center related to one of three equivalent broken Si-N basal bonds. A more recent calculation predicted no DX-like behavior for Si in AlN and suggested that the n-type conductivity in AlN is caused by the cluster of four Si and an Al vacancy, V Al -4Si, which is predicted to have a formation energy lower than that of the substitutional Si Al donor.…”
Section: Stable and Metastable Si Negative-u Centers In Algan And Alnmentioning
confidence: 99%
“…O N in AlN is commonly associated with deep levels, which affect the position of the Fermi level and counteract the electrical activity of any other donors. 8,9 Alternatively, it has been suggested that oxygen incorporation does not have a negative effect in achieving n-type Al x Ga 1Àx N (x $ 0.60), but rather enhances the conductivity. 2 The speculated Si transition from shallow donor in GaN to a localized deep DX center in Al x Ga 1Àx N alloys with increasing Al content is under a continuing debate following first-principle calculations of substitutional silicon (Si Al ) in AlN.…”
mentioning
confidence: 99%
“…2 The speculated Si transition from shallow donor in GaN to a localized deep DX center in Al x Ga 1Àx N alloys with increasing Al content is under a continuing debate following first-principle calculations of substitutional silicon (Si Al ) in AlN. 8,9 Issues of major relevance to the n-type conductivity of high-Al-content Al x Ga 1Àx N alloys associated with Si and O incorporation, their shallow donor or deep donor level (DX) behavior, and carrier compensation sustain a subject of controversy and a better understanding is yet to emerge. The present study aims at incorporation kinetics study of Si and O in high-Al-content Al 0.77 Ga 0.23 N layers, especially with Si doping that can produce efficient carrier concentration.…”
mentioning
confidence: 99%